Clinical efficacy observation and safety evaluation of acupuncture for intractable facial paralysis: a single-blinded randomized controlled pilot trial - Xie, Hongyu; Xia, Yu; Zhang, Lele; Yuan, Aihong; Yang, Jun; Cheng, Ling; Gao, Ting; Li, Bo; Yuan, Xuwen; Ye, Min; Kan, Wenjing; Shi, Jie; et al. (Frontiers in Neurology, 2025)
IntroductionAcupuncture can effectively improve the clinical symptoms of intractable facial paralysis (IFP). However, it is not yet clear whether the use of acupuncture manipulation affects the therapeutic effect. This study aims to conduct a preliminary exploration of the clinical efficacy and safety of acupuncture treatment for IFP using acupuncture manipulation.MethodsA single-center, single-blind, randomized controlled pilot trial was conducted from December 2022 to December 2023, involving 40 IFP participants, divided into the ordinary acupuncture group (OAG, n = 20) and the characteristic acupuncture group (CAG, n = 20). The OAG underwent a standardized acupuncture protocol comprising 3 weekly sessions over a 10-week period. This structured regimen included 3 consecutive treatment cycles (10 sessions/cycle), culminating in 30 total therapeutic interventions. The CAG has performed characteristic acupuncture manipulation on this basis, with the same frequency and duration of treatment as the OAG. Assess the patient’s facial recovery status at baseline and after 10, 20, and 30 treatments.ResultsAfter the second treatment course, the difference in the Anzhong Facial Paralysis Precision Scale (Oral Commissure Ptosis Grading Scale) levels between the two groups began to show statistical significance (p < 0.05); After the third treatment course, the scores changes in Sunnybrook Facial Grading System (SFGS) scale between the two groups began to show statistical significance (p < 0.05); After the first treatment course, there was statistical significance in the average ratio changes at LI20 (Yingxiang) and ST4 (Dicang) between the two groups (p < 0.05). After the second treatment course, statistical significance in the average ratio changes was observed at GB14 (Yangbai), SI18 (Quanliao), LI20 (Yingxiang), and ST4 (Dicang) between the two groups (p < 0.05). After the third treatment course, statistical significance in the average ratio changes was found at all acupoints between the two groups (p < 0.05). Consequently, the CAG group demonstrated superior therapeutic efficacy compared to the OAG group.ConclusionAcupuncture has a good therapeutic effect on IFP, and the combination of characteristic acupuncture manipulation has a better therapeutic effect. However, these conclusions require further validation in larger clinical studies.Clinical trial registrationhttps://www.chictr.org.cn/, Identifier ChiCTR2200065442.